A New Method and Mass-Spectrometric Instrument for Extraterrestrial Microbial Life Detection Using the Elemental Composition Analyses of Martian Regolith and Permafrost/Ice - Managadze, G.G.; Safronova, A.A.; Luchnikov, K.A.; Vorobyova, E.A.; Duxbury, N.S.; Wurz, Peter; Managadze, N.G.; Chumikov, A.E.; Khamizov, R.Kh. (Astrobiology, 2017)
We propose a new technique for the detection of microorganisms by elemental composition analyses of a sample extracted from regolith, permafrost, and ice of extraterrestrial bodies. We also describe the design of the ABIMAS instrument, which consists of the onboard time-of-flight laser mass-reflectron (TOF LMR) and the sample preparation unit (SPU) for biomass extraction. This instrument was initially approved to fly on board the ExoMars 2020 lander mission. The instrument can be used to analyze the elemental composition of possible extraterrestrial microbial communities and compare it to that of terrestrial microorganisms. We have conducted numerous laboratory studies to confirm the possibility of biomass identification via the following biomarkers: P/S and Ca/K ratios, and C and N abundances. We underline that only the combination of these factors will allow one to discriminate microbial samples from geological ones. Our technique has been tested experimentally in numerous laboratory trials on cultures of microorganisms and polar permafrost samples as terrestrial analogues for martian polar soils. We discuss various methods of extracting microorganisms and sample preparation. The developed technique can be used to search for and identify microorganisms in different martian samples and in the subsurface of other planets, satellites, comets, and asteroids—in particular, Europa, Ganymede, and Enceladus.